FORMULASI SEDIAAN GEL EKSTRAK ETANOL BUNGA KUBIS MERAH (Brassica oleracea L.) SEBAGAI ANTIOKSIDAN DENGAN METODE DPPH - Ferry Effendi; M Ikhwan Setiawan; Ayu Lestari (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2019)
Red cabbage flower (Brassica oleracea L.) contains antioxidant compounds with strong activity potential. This research aims to make antioxidant gel preparations using HPMC as a base gel containing red cabbage flower extract with concentrations (% b/b) for F1, F2 and F3 are 5%, 7,5% and 10%, which are then evaluated and tested its antioxidant activities. Testing antioxidant activity is carried out by the determination method of IC50 using the reagent DPPH (Difenil-2-Pikrilhidrazil). From research acquired the value of IC50 for ethanol extract red cabbage flower and vitamin c as comparative compounds is 47,10 ppm and 6,30 ppm. Antioxidant activity of red cabbage flower ethanol extract in gel preparations in each formulation has a IC50 value of 80,15 ppm (F1), 59,71 ppm (F2), and 57,48 ppm (F3). Evaluation ofgel preparation includes homogenity, organoleptic, viscosity and pH. The physical properties test results of gel dosage showed that all the preparations of the homogeneous gel, have a pH between the 5,30-5,70 corresponding to the skin pH, with a viscosity value of 3000-3700 cps, and have a coverage of ≤ 7 cm. Based on the results of this study, it was concluded that red cabbage flower ethanol extract can be formulated in an antioxidant gel with the best concentration is 10%.